FROM TAFSIR TO TADABBUR: A PRELIMINARY SURVEY OF SAUDI SCHOLAR’S TRENDS IN UNDERSTANDING THE QUR’AN - Ridho, Ahmed Zaranggi Ar (Sekolah Tinggi Agama Islam Sadra, 2024)
This article aims to look at the history of tadabbur knowledge in Saudi Arabia as an alternative trend in understanding the Qur’an in the contemporary era. The study of Qur’anic reading dominated by hermeneutical-contextual discourse ignores other responses to the complexity of understanding and applying Qur’anic content. The stagnation of the development of Qur’anic interpretation in Saudi Arabia is not entirely true. One form of response that has become a trend is the recitation of tadabbur al-Qur’ān. This is indicated by the massive publication of various books on tadabbur in the last twenty years (2000–2020), which symbolizes the alternation of Saudi Arabian scholars in responding to contemporary interpretive discourse. Tadabbur inspiration can be found in three works of tafsir written by Saudi scholars beginning with ‘Abdurraḥmān Sa‘dī, Shaykh Uthaimīn, and Shaykh Sulaymān al-Lāḥīm. Through a survey and brief review of the idea of tadabbur in the knowledge network of Qur’anic exegesis in Saudi Arabia, this study found three main trends. First, the influence of Salafi ideology as an idea that underlies the dissemination of the concept of Qur’anic tadabbur. Second, revitalization efforts were made by ‘Abdurraḥmān Ḥabannakah in making tadabbur a separate discipline. Third, as a response to the diversity of contextual-applicative approaches dominated by the hermeneutic approach to the Qur’an. These three trends become a form of methodological response of Saudi Arabian scholars to the discourse of reading the Qur’an that developed in the contemporary era.